Pengaruh Pengetahuan Kewirausahaan, Karakteristik Kewirausahaan dan Inovasi Produk Terhadap Kinerja Usaha Mikro, Kecil dan Menengah - Putri, Ayu Rahma; Muis, Indra (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The micro, small, and medium-sized enterprise (MSME) sector in Indonesia faces a relatively high failure rate, with a failure rate of 25% in the first two years and over 80% by the third year. This study examines the influence of entrepreneurial knowledge, entrepreneurial characteristics, and product innovation on the business performance of key MSME actors in Bekasi City. A quantitative method with purposive sampling and accidental sampling was used on 102 respondents. The results indicate that the variables of entrepreneurial knowledge and product innovation have a positive and significant influence (p<0.001), with a dominance factor (β=0.356), whereas the variable of entrepreneurial characteristics has a positive but insignificant influence (p>0.329). Together, these three variables explain 28.3% of the variation in business performance (R² = 0.283). These findings underscore the importance of an entrepreneurial knowledge approach in the business world, particularly the strengthening of training on the essential traits every business owner must possess achieved through government-community.